MEMBUMIKAN BUDAYA HUKUM PANCASILA MELALUI REVOLUSI MENTAL UNTUK PENGUATAN INTEGRITAS APARATUR PERADILAN - Dewantoro (Mimbar Hukum, 2024)
As a legal state founded on the Pancasila ideology, Indonesia undertakes various activities to develop its legal system. This includes enhancing the internal legal culture among law enforcement officials, particularly within judicial institutions. Pancasila provides values and guidelines for national and state conduct, emphasizing that all actions, both within and outside official judicial roles, should reflect these noble values. Indonesian judges are expected to demonstrate high integrity, aligning their conduct with Pancasila. However, recent allegations of corruption within judicial institutions indicate that the judicial apparatus has not fully embraced Pancasila values. This gap in the legal culture suggests a lack of adherence to these principles. Doctrinal juridical research has concluded that the National Movement of Mental Revolution is crucial for revitalizing and embedding Pancasila values within judges and the judicial apparatus. This revitalization aims to restore public trust and encourage the general public to emulate the attitudes and behavior of the judiciary, thereby implementing Pancasila values in daily activities and reinforcing the concept of a Pancasila-based legal state.